Experimental investigation of CF8 stainless steel impeller quality using PLA-based fused deposition modeling-assisted investment casting - Margi Shah; Dhiren Patel; Sarang Pande; Mustufa Haider Abidi; Fahad Alasim (Materials Research Express)
The conventional Investment Casting (IC) process is extensively used for manufacturing parts with intricate shapes and complex geometries. However, its drawbacks include long cycle times and costly tooling, making it ideal for mass production but inefficient for frequent design changes, small batch production, or customized products. To address these challenges, a novel hybrid method known as Fused Deposition Modeling Assisted Investment Casting (FDMAIC) has been developed. In FDMAIC, the wax pattern is replaced by an FDM-printed pattern, while all other steps follow the conventional IC process. In this study, a semi-open impeller for a centrifugal pump was produced using FDMAIC, with Polylactic Acid (PLA) as the pattern material and CF8 for casting. Dimensional accuracy and surface roughness, key indicators of quality, were evaluated at both the printing and casting stages. Critical dimensions such as outer and inner diameters, shroud and blade thicknesses, and total height were measured, along with surface roughness at the shroud and blade surfaces. In the final cast, maximum dimensional deviation was observed in Outer diameter(−2.408 mm), and minimum dimensional deviation was observed in total height(−0.169 mm). The surface roughness values obtained at the shroud and blade surface of the final cast were 4.64 μm 6.67 μm, respectively. Microstructure and hardness testing were also performed on the FDMAIC impeller to validate the process. The results provide detailed insights into the feasibility of FDMAIC and suggest areas for further improvement.